Saved information is remembered less well than deleted information, if the saving process is perceived as reliable. Issue 9 (21st October 2021) - Schooler, Joel N.; Storm, Benjamin C.
ABSTRACT: Prior research has shown that people are more likely to remember information that is deleted from a computer than information that is saved on a computer, presumably because saving serves as a form of cognitive offloading. Given recent concerns about the robustness and replicability of this "Google Effect, " we conducted two experiments seeking to replicate and extend the phenomenon by identifying a potential boundary condition for when it is observed. In Experiment 1, we replicated the Google Effect, but only when participants experienced a practice phase demonstrating the reliability of the saving process. No evidence of a Google Effect was observed when participants experienced a practice phase demonstrating the saving process to be unreliable. In Experiment 2, we replicated the results of Experiment 1 in the reliable condition, while demonstrating the effect to be robust across 10 different topics of trivia statements. Taken together, these results suggest that the Google Effect is a replicable phenomenon, but that the perceived reliability of the saving process is critical for determining whether it is observed.